Information professionals' competency model for public sector / Azrilah Abdul Aziz - Abdul Aziz, Azrilah (2009)
Information Professionals (IP) handles information in various forms, so does the technology involved. IP are seen as specific personnels involved with handling of information on a digital landscape. The IPs are commonly associated with, professionals from various fields but not limited to; technology, educations, business, and management. Information and technology based products are highly sought by users and organizations for their decision making process to achieve better economic wealth. This has shifted the paradigm expected on IP competency within organizations. Possessing educational and technical knowledge alone are no more assurance of securing good employment, but it requires further skills that contribute to the performance of an IP in the dynamic information age. In this thesis, competency framework from various professionals' bodies and industries alike were reviewed and consolidated in the effort of constructing the IP Competency Model, encompassing most professions that use information and technology in their conduct of business. A face validation process was done to validate the IP Competency Model. This will be used in monitoring the competency of an IP to ensure proper training can be developed and convenient redeployment exercise could be carried out with ease in gaining optimal benefit from the IPs. Subsequently, an IP Competency Assessment Tool (IPCAT) is developed to measure the competency attributes and to establish an IP profile effortlessly. IPCAT comprises of tasks termed as operational definition based on selective attributes as keywords derived from the IP Competency Model describing each competency traits. IP personnel from selected agencies and organizations participated in the exercise to validate the IPCAT as the assessment tool by using Rasch methodology. Responses from the validation serve as the measure, which reflects their ability in carrying out their daily operation. The study revealed that Malaysian IP have three conspicuous profiles; those are aspiring male IP that shows high competency with average 2.59logit, the average competency of male top management with 0.334logit, and low competency IP are female professionals that have long working years but in the subordinate management rank with average -0.20logit. This measurement enables organization's decision making on promotion, placement and redeployment exercise to be done more objectively. This new model of measurement assessment put classical resource management to a new paradigm.